2023
DOI: 10.54910/sabrao2023.55.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Variations in Catharanthus Roseus L. Induced by Gamma Rays and Sodium Azide Using Rapd Markers

Abstract: The study of genetic variations in Catharanthus roseus L. induced by gamma rays and sodium azide using RAPD markers transpired in 2021–2022 at the Department of Biology, University of Kufa, Iraq. The seeds of two cultivars of Catharanthus roseus L., i.e., victory pure white and local (pink variety), received two doses of gamma rays (50 and 75 Gray) and four sodium azide concentrations (0.2%, 0.4%, 0.6%, and 0.8%). Non-treated seeds of both cultivars also served as a control for comparison. Evaluating the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The presented results corresponded to previous research, which showed that the stem cutting length significantly affected the rooting efficiency; higher rooting efficiency (rooting percentage) appeared with a stem cutting length of 20 cm for miniature rose plants (Bredmose et al, 2004;Al-Mathidy et al, 2023). A higher rooting percentage emerged with 7 cm minirose bush cuttings, while the rooting percentage reduction used shorter cuttings (Pirola et al, 2016;Al-Musawi et al, 2023). Recently, utilizing the IBA (Vapor Gard) in research studies sought to protect plants from desiccation and fungal infections (Latocha et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The presented results corresponded to previous research, which showed that the stem cutting length significantly affected the rooting efficiency; higher rooting efficiency (rooting percentage) appeared with a stem cutting length of 20 cm for miniature rose plants (Bredmose et al, 2004;Al-Mathidy et al, 2023). A higher rooting percentage emerged with 7 cm minirose bush cuttings, while the rooting percentage reduction used shorter cuttings (Pirola et al, 2016;Al-Musawi et al, 2023). Recently, utilizing the IBA (Vapor Gard) in research studies sought to protect plants from desiccation and fungal infections (Latocha et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The rose, considered one of the most valued ornamental woody plants, has antioxidant and anti-inflammatory properties, widely used as a horticultural and medicinal plant, hence, having a vast economic value worldwide (Scalliet et al, 2008;Zhu et al, 2015;Xiang et al, 2017). The Rosa L. is one of the largest genera, with alternate, stipulate, palmate, or pinnate leaves and flowers distinguished by their colorful appearance and flowering nature (Xiang et al, 2017;Al-Mathidy et al, 2023;Al-Musawi and Al-Tamimi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various studies tried to enhance their biosynthesis in plant tissues using biotechnological strategies in vitro cultures (Zhu et al, 2015). In this regard, several alkaloids' extraction from C. roseus in vitro served pharmaceutical uses (Naeem et al, 2017;Al-Haidari and Al-Tamimi, 2023;Al-Musawi and Al-Tamimi, 2023).…”
Section: Introductionmentioning
confidence: 99%